GE_GERICHTE P/13805/2007 vom 14. Dezember 2018 - GE Cour de justice (2018)
CRÉANCE ; CONFISCATION(DROIT PÉNAL) ; TIERS NON IMPLIQUÉ ; ACTION PÉNALE ; PRESCRIPTION ; CALCUL DU DÉLAI ; PRÉSOMPTION D'INNOCENCE | CP.70; CP.71; CP.97; CP.98; CPP.426; CPP.429